Remittance inflows and state-dependent monetary policy transmission in developing countries - Immaculate Machasio; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2016)
Remittance inflows from overseas workers are an important source of foreign funding for developing and emerging economies. The literature is in- conclusive about the cyclical nature of remittance inflows. To the extent remittances are procyclical they pose a challenge to monetary policy: a tightening of policy will be less effective if at the same time remittances increase strongly. The same is true for a policy easing under exceptionally weak remittance inflows. This paper estimates a series of nonlinear (smooth-transition) local projections to study the effectiveness of monetary policy under different remittance inflows regimes. The model is able to provide state-dependent impulse response functions. We show that for Kenya, Mexico, Colombia and the Philippines monetary policy indeed has a smaller domestic effect under strong inflows of remittances. These results have important implications for the design of inflation targeting in developing countries.
Keywords: E52; E32; O16; 330; remittance inflows; monetary policy; inflation targeting; smooth-transition model; local projections